(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Gautan R, Baral N, Sharma HP. 2022. Are white-rumped vultures (Gyps bengalensis) scavengers or predators at a vulture safe feeding site of Nepal?. Biodiversitas 23: 3808-3812. Establishing safe feeding sites has been promoted as a strategy to conserve wild vultures following the population crash in South Asia due to the contamination of natural food by veterinary diclofenac. Several feeding sites have been established in the region, including Nepal and it is important to evaluate their effectiveness. One aspect that is not clear yet is whether such safe feeding sites change the behaviors of wild vultures in South Asia. Here, we report incidents of White-rumped Vultures Gyps bengalensis attacking live animals at the Vulture Safe Feeding Site in Ghachok village in central Nepal. Even though a carcass was available nearby to feed upon, three White-rumped Vultures attacked an adult cow and a calf at the feeding site. The vultures’ attack served as an ancillary cause of the calf’s death in this case. These two incidents of vultures’ attacking live animals at the safe feeding site may allude to changing behaviors and cast doubt on their status of being classified as an obligate scavengers. The findings suggest alteration of vulture behaviors at the safe feeding site. Further research is needed to test the hypothesis of vulture behavior change.